Bhutan : Technical Assistance Report-Report on the External Sector Statistics Technical Assistance Mission (April 2-13, 2018). (IMF Staff Country Reports; Country Report ;, 2018)
As part of the IMF-South Asia Regional Training and Technical Assistance Center (SARTTAC) work program, a technical assistance (TA) mission on external sector statistics (ESS) was conducted during April 2-13, 2018. The mission assisted the Royal Monetary Authority (RMA) in compiling and disseminating external debt statistics (EDS) consistent with the international investment position (IIP), reviewed the compilation method of direct investment statistics, and assessed the coverage of external flows related to hydropower projects.